Sentinel node detection in muscle-invasive urothelial bladder cancer is feasible after neoadjuvant chemotherapy in all pT stages, a prospective multicenter report - Rosenblatt, Robert (World J Urol, 2016)
PURPOSE: To determine whether sentinel node detection (SNd) in muscle-invasive urothelial bladder cancer (MIBC) can be performed in patients undergoing neoadjuvant chemotherapy (NAC) and determine whether SNd is feasible in all pT stages, including pT0. BACKGROUND: Previous published series of SNd in MIBC have not included patients undergoing NAC, and systematic reports of pT0 patients w/wo NAC were absent. Translational immunological tumor research on MIBC focusing on SNd, in the era of NAC, requires technical feasibility. Additionally, SNd in MIBC requests further evaluations as a method for nodal staging. MATERIALS AND METHODS: Ninety-nine patients with suspected urothelial MIBC were prospectively selected from six urological centers. After TUR-B and primary staging, 65 MIBC patients qualified for radical cystectomy. Precystectomy staging was cT2a-T4aN0M0, including 47 NAC patients and 18 chemo-naïve patients. All 65 patients underwent intraoperative SNd by peritumoral injection of 80 Mbq Technetium and Geiger probe detection. Postcystectomy staging was pT0-T4aN0-N2M0. SNs were defined by two calculations, SNdef1 and SNdef2. RESULTS: Totally 1063 lymph nodes were removed (total SNs; 222–227). NAC patients with pT0 (n = 24) displayed a true positive detection in 91.7 % by either SNdef, with a median of 3.0 SNs. NACpT >0 patients had a true positive detection in 87 % (SNdef1) and 91.3 % (SNdef2). In a univariate analysis, patient group neither NAC nor tumor downstaging influenced detection rates, regardless of SN definition. In total eight patients, 4/22 metastatic nodes were SNs while 18/22 were non-SNs. CONCLUSIONS: Sentinel node detection in MIBC is feasible also in NAC patients, regardless of pT stage. SNd played no role in nodal staging.